2010
DOI: 10.1002/ajmg.a.33307
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variability and novel neurodevelopmental findings in 49, XXXXY syndrome

Abstract: 49, XXXXY is a rare chromosomal syndrome due to double nondisjunction of the replicating X chromosome. Considered a severe variant of XXY or Klinefelter syndrome, boys with this chromosome constitution are assumed to have severe mental retardation (MR) in addition to craniofacial, genital, endocrine, and heart abnormalities. Here, we present a multidisciplinary analysis including the clinical and neurobehavioral aspects of this condition in 20 boys with 49, XXXXY who share a common phenotype and neurobehaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 18 publications
2
76
0
3
Order By: Relevance
“…In fact, the majority of children with 49, XXXXY have relatively intact nonverbal and also receptive vocabulary and comprehension skills 5 . Neurological examination and neuropsychological testing in our patient was consistent with this neurocognitive profile.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the majority of children with 49, XXXXY have relatively intact nonverbal and also receptive vocabulary and comprehension skills 5 . Neurological examination and neuropsychological testing in our patient was consistent with this neurocognitive profile.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic abnormalities affect activities of daily living, mobility, neurodevelopmental progression, and ultimately, quality of life. In an effort to aid clinicians and families with the early identification of musculoskeletal anomalies, this article sought to survey the common musculoskeletal anomalies in this population and to expand data on birth weight, birth height, etc., that have been previously presented by Gropman et al [2010].…”
Section: Introductionmentioning
confidence: 69%
“…At birth, subtle facial dysmorphism may be noted, such as epicanthal folds, upslanting palpebral fissures, or full upper eyelids [Simpson et al, 2003;Visootsak, 2007;Gropman et al, 2010;Samango-Sprouse et al, 2011;Tartaglia et al, 2011]. Associated orthopedic abnormalities include congenital hip dysplasia, torticollis, radioulnar synostosis, congenital talipes equinovarus (club foot), and clinodactyly [Barr et al, 1962;Okuyama, 1993;Linden et al, 1995;Cammarata et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have reported that cognitive delays were not as significant as described in the past and personalities and learning styles are similar to 47,XXY cases [SamangoSprouse, 2001;Visootsak et al, 2001Visootsak et al, , 2007Visootsak and Graham, 2006;Gropman et al, 2010]. Variability in clinical and cognitive functioning may reflect skewed X inactivation, mosaicism, or other factors that warrant further investigation [Gropman et al, 2010]. Recently, Ottesen et al [2010] reported a study about the increased height in patients with additional sex chromosomes.…”
Section: Other Numeric Sex Chromosome Abnormalitiesmentioning
confidence: 95%